Effectiveness of West Lombok Regency Hotel and Restaurant Tax Revenue - Al Farisi, Moh Salman; Eikman, Alfian; Hadi, Sulhan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
A developed region is the goal of development. Progress is meant here to be advanced economically, socially and the advancement of human resources owned by the region. Meanwhile, development is meant to build society as a whole, namely development that covers all aspects of society's life that can function. harmony and balance in all fields in order to create a just and prosperous society that is equally material and spiritual.This research uses descriptive analysis methods. The calculation of the numbers uses the formula for contribution, effectiveness, and measuring the efficiency ratio. Contribution Analysis is an analysis used to find out how much contribution can be made from Hotel and Restaurant tax revenues to the Original Regional Income of West Lombok Regency. Overall, for the hotel sector, tax levies in West Lombok Regency are in the ineffective category, because the actual tax that can be achieved is almost always below the predetermined target, with the exception of restaurant tax, the tax levy collected exceeds 100% or exceeds the predetermined target in the year 2022 and 2022 tax collection is in the very effective category.